2013
DOI: 10.1155/2013/403507
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Rupture of a False Aneurysm after Femoral Arterial Catheterization: Unexpected Delay after a Common Procedure

Abstract: We report the case of a 79-year-old patient who presented with a femoral iatrogenic pseudoaneurysm of delayed and unusual onset with immediately life-threatening massive bleeding. Ultrasound is the method of choice for the diagnosis of pseudo aneurysm. If there is not spontaneous closure, ultrasound-guided compression repair, minimally invasive percutaneous treatments, and surgical repair are the three therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Pseudoaneurysm is a collection of blood formed as a result of a vascular wound and retained in the tissues surrounding the breached vessel [1]. Pseudoaneurysm of the femoral artery is uncommon [2].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoaneurysm is a collection of blood formed as a result of a vascular wound and retained in the tissues surrounding the breached vessel [1]. Pseudoaneurysm of the femoral artery is uncommon [2].…”
Section: Discussionmentioning
confidence: 99%
“…Rupture of femoral pseudoaneurysms has been scarcely reported in the medical literature, either due to the rarity of the condition or the unwillingness to report a major iatrogenic complication. There has been a report of ruptured pseudoaneurysm after femoral arterial catheterization for continuous hemodynamic monitoring and multiple blood sampling, in a patient hospitalized in the intensive care unit [ 6 ], as well as a post-atherectomy superficial femoral artery pseudoaneurysm [ 7 ]. There have also been reports of ruptured femoral artery pseudoaneurysms, complicated with infection in drug addicts [ 8 - 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…But there are a few cases in the literature which is shown that post-catheterization pseudoaneurysms can develop after 12 days from intervention [5].…”
Section: Discussionmentioning
confidence: 99%